Nemško-slovenski zgodovinski glosar ali Poskus pisanja glosarja na področju humanistike oz. družboslovja - Hudelja, Niko (Vestnik za tuje jezike, 2011)
The author first defines the role of history as a constituent part of the humanities and the social sciences, explaining its connection with other, related scientific disciplines. On the basis of this, he presents the criteria of his selection of terms for the historical glossary. His preference is a compromising approach, which means inclusion of semi-terms and non-terms, since he believes that in the selected field of science it is impossible to consistently comply with the definition of terminology. The paper then discusses the entries in the glossary, distinguishing between the central and the peripheral part of historical terminology. The author is convinced that such an approach, in addition to its other advantages, is also very user-friendly.
Keywords: German; nemščina; Slovene; slovenščina; history; zgodovina; slovarji; dvojezični slovarji; glosarji; strokovni slovarji; terminologija; terminology